Nanostructured Platform Based on Graphene-polypyrrole Composite for Immunosensor Fabrication. (2017) - Cernat, Andreea; Tertiș, Mihaela; Păpară, Claudia Nicoleta; Bodoki, Ede; Săndulescu, Robert
Abstract: A hybrid graphene-polypyrrole (PPy) composite-based platform was elaborated by using nanosphere lithography structuration. This platform was further used for the antibody anti-acetaminophen immobilization in order to obtain an immunosensor for selective detection of paracetamol (acetaminophen) by using electrochemical methods. After patterning of the composite layer, the five-fold improvement of electrochemical signal was observed, suggesting that a higher amount of antibody was immobilized. This strategy permitted the ease and controlled immobilization of bioreceptors on the composite graphene-PPy platform and enhanced the sensitivity for paracetamol detection.